2002
DOI: 10.1016/s0009-2614(02)00804-7
|View full text |Cite
|
Sign up to set email alerts
|

Spin dynamics and zero-field splitting constants of the triplet exciplex generated by photoinduced electron transfer reaction between erythrosin B and duroquinone

Abstract: The spin dynamics of the duroquinone anion radical generated by photoinduced electron transfer reactions from triplet erythrosin B to duroquinone has been studied by using transient absorption and pulsed FT-EPR spectroscopy. Triplet exciplex formation as the reaction intermediate is verified by the observation of spin-orbit coupling induced electron spin polarization. The kinetic parameters for exciplex formation and the intrinsic enhancement factors of electron spin polarization are determined in various alco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…Similar results were found for excited state quenching of phenothiazine dyes by p-benzoquinones in polar solvents [12]. Later on, Kubota et al, during their measurements of eosin/quinones and erythrosin/quinones systems with time resolved and pulse electron pair resonance, EPR, have found that a triplet exciplex is formed as the leading intermediate in the PET reactions in slightly polar solvents [13][14][15].…”
Section: Introductionsupporting
confidence: 67%
See 2 more Smart Citations
“…Similar results were found for excited state quenching of phenothiazine dyes by p-benzoquinones in polar solvents [12]. Later on, Kubota et al, during their measurements of eosin/quinones and erythrosin/quinones systems with time resolved and pulse electron pair resonance, EPR, have found that a triplet exciplex is formed as the leading intermediate in the PET reactions in slightly polar solvents [13][14][15].…”
Section: Introductionsupporting
confidence: 67%
“…Tero-Kubota et al proposed the spin orbital coupling, SOC, mechanism as a new chemically induced dynamic electron polarization, CIDEP, mechanism [14,15]. Steiner explained the remarkable magnetic field effect, MFE on the PET reBrought to you by | University of Georgia Libraries Authenticated Download Date | 6/10/15 9:05 PM action of thionine with halogenated aniline derivatives as sublevel selective back electron transfer reaction as a result of SOC interactions between triplet exciplex or contact radical pair, RP, and the ground state [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…48,70,73,123 This assumption for the initial conditions is valid when ∆G CS > -1 eV for the forward ET reactions. 124 Inclusion of the effect of the long-range Coulomb attraction field F(r) has been found to affect the magnitude of calculated P RPM in this study; P RPM magnitudes became smaller by 30-40% than P RPM values calculated without taking account the This result may be consistent with the theoretical studies predicted by Pedersen et al 51 In addition to the Coulomb field effect, solvation structure due to a potential of mean force of U(r) ) -k B T ln{g(r)} is known to influence the mutual diffusional motions.…”
Section: Finallymentioning
confidence: 99%
“…Study of the photochemical behavior of quinone molecules, for example p-benzosemiquinone, anthracenequinone, and naphthoquinone, have generated much interest in simulating photosynthesis research on the purinaquinone system [4][5][6][7][8][9][10]. For the photosensitive molecule duroquinone (DQ), reported studies have mainly focused on the duroquinone anion radical DQ •2 generated by photoinduced electron transfer in DQ-electron-donor systems because DQ is a relatively powerful one-electron oxidant [11][12][13]. However, Roger H. Bisby et al observed DQH • , which is generated by hydrogen atom transfer from 6-palmitoyl-L-ascorbic acid (PASCH 2 ) or a-tocopherol to 3 DQ, followed by deprotonation of DQH • to DQ •2 , by use of transient absorption spectroscopy and timeresolved resonance Raman spectroscopy [14].…”
Section: Introductionmentioning
confidence: 99%